Manajemen Mitigasi Bencana Menggunakan Teknologi Balloon Tethered - Nining Nirmalasari; Junaiti Sahar (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Introduction: The occurrence of natural disasters in Indonesia from year to year continues to occur, with the progress of communication technology that is increasingly expected to be able to facilitate communication when a disaster occurs. Such as the use of balloon tethered technology that can function for disaster mitigation, with the use of balloon tethered that is tethered in areas that are at risk of disaster prone. Methods: The method used by the author was literature review. The database used by the author were Google Scholar, IEEE Xplore, GEOECO, EBSCOhost, Researchgate and the keywords were disaster mitigation, Tethered Balloon technology, Aerial Platform. Results: This tethered balloon technology consists of a combination of flying balloons, tethered, and payload, for the use of disaster mitigation and supports faster broadband communication networks to users before or during and after a disaster. The rescue team can work more effectively and efficiently with the help of this tethered balloon technology. Conclusion: Cross-sectoral collaboration involving various disciplines is needed for disaster mitigation management. The role of the government is very large for the availability of communication technology such as tethered balloons. Keywords: disaster mitigation; tethered balloon; platform ABSTRAK Pendahuluan: Kejadian bencana alam di Indonesia dari tahun ke tahun terus terjadi, dengan adanya kemajuan teknologi komunikasi yang semakin berkembang diharapkan dapat memudahkan komunikasi saat terjadi bencana. Seperti pada penggunaan teknologi balon tethered yang dapat berfungsi untuk mitigasi bencana, dengan penggunaan balon tethered yang ditambatkan di daerah yang beresiko rawan bencana. Metode: Metode yang digunakan penulis adalah literature review. Database yang digunakan penulis adalah Google Scholar, IEEE Xplore, GEOECO, EBSCOhost, Researchgate dengan mitigasi bencana, tehnologi Tethered Balloon, Aerial Platform. Hasil: Teknologi balon tethered terdiri atas gabungan balon terbang, tethered, dan payload, untuk penggunaan mitigasi bencana dan mendukung jaringan komunikasi broadband yang lebih cepat kepada pengguna sebelum atau selama dan sesudah bencana. Tim penyelamat dapat bekerja lebih efektif dan efisien dengan bantuan teknologi balon tethered ini. Kesimpulan: kerjasama lintas sektoral yang melibatkan berbagai disiplin ilmu dibutuhkan untuk manajemen mitigasi bencana. Peranan pemerintah sangat besar untuk ketersediaan teknologi komunikasi seperti balon tethered ini. Kata kunci: mitigasi bencana; tethered balloon; platform